2016
DOI: 10.5530/ijmedph.2016.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drug Usage Pattern during Pregnancy at a Tertiary Care Teaching Hospital

Abstract: Objectives:To assess the usage of drugs during pregnancy in the OBG Department at a tertiary care teaching and research hospital in Bangalore city, India. Materials and Methods: Data was retrieved from participant's (n = 250) case sheets of OBG department, on daily basis during a period of 7 months. Data was collected during their visit to the hospital and admission for safe confinement, which included demographic details, list of drugs taken, categorization of drugs based on USFDA, ATC and class of drugs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…In the current finding there was no drug used from FDA category X. This was similar with the study conducted in Adama [1], northern Ethiopia [8] and Banglore [36]. Studies indicated that there was a practice of prescribing drugs from category X in Omani (0.3%) [9], in Brazil (0.03%) [28], in Jimma, Ethiopia (7.4%) [10], in Bahirdar, Ethiopia (5.5%) [12], and in United States (4.6%) [11].…”
Section: Discussionsupporting
confidence: 91%
“…In the current finding there was no drug used from FDA category X. This was similar with the study conducted in Adama [1], northern Ethiopia [8] and Banglore [36]. Studies indicated that there was a practice of prescribing drugs from category X in Omani (0.3%) [9], in Brazil (0.03%) [28], in Jimma, Ethiopia (7.4%) [10], in Bahirdar, Ethiopia (5.5%) [12], and in United States (4.6%) [11].…”
Section: Discussionsupporting
confidence: 91%
“…1,2 Medications such as folic acid, vitamins, iron, and others may be needed to supplement mothers' diet or to manage co-morbid illness such as diabetes mellitus, malaria, urinary tract infection, hypertension, Human Immune-deficiency Virus (HIV) infection, or mental illness. 3,4 Rational medications use during pregnancy has always created a challenge in antenatal care due to the potential risk associated with use, both to the mother and the foetus. 5 Drug utilization studies have revealed that a high proportion of women use medications during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the use of prescription medications and other over the counter drugs should be avoided during pregnancy. However, it is unlikely to avoid all drugs during pregnancy because this may put both the mother and fetus in danger from complications of untreated acute and chronic medical disorders such as epilepsy, diabetes mellitus, thyroid disorder, severe depression, hypertension, and bronchial asthma [4,5]. Besides, respiratory infections, headaches, constipation, nervousness, and other common complaints that occur during pregnancy may also need drug treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted in various parts of developed [20][21][22][23][24] and developing countries [5,10,[25][26][27] to assess drug utilization patterns during pregnancy. Despite the limited information available on the safety and effectiveness of drugs in pregnancy, a large proportion of those studies reported that health care professionals prescribe and pregnant mothers consume a surprisingly large number of drugs.…”
Section: Introductionmentioning
confidence: 99%